A interlocução entre teoria e prática pelo olhar reflexivo através de Relatos de Experiência no Programa Residência Pedagógica do Curso de Licenciatura em Química - OLIVEIRA, Beatriz Sousa (2023)
This Final Course Work adheres to the structure established in Normative Instruction No. 01/2023 of the Pro-Rectory of Undergraduate Education at the Federal University of Pará. This normative regulates the activities related to the CBT, adapting them flexibly in response to the implications caused by the COVID-19 pandemic. In this way, the reports submitted to CAPES over the course of 12 months on my career as a Pedagogical Residency Program (PRP) fellow will be used. That said, my report explores the theme of "Fantastic Women Scientists and the Chemical Elements" with the Future Scientists Program. I also analyze different didactic proposals for teaching, focusing on the question "What do balloons have to do with teaching chemistry?" which corresponds to a methodology carried out with 3rd year high school classes to review the content on hydrocarbons at the PRP field school. To summarize, these two reports differ in their emphasis: the first focuses more on research, while the second concentrates on teaching practice. As a future chemistry teacher, I am deeply grateful for having the opportunity to take part in the Pedagogical Residency Program (PRP). This initiative offers a practical learning environment that has enriched my training journey and allowed me to continue evolving professionally.